Complications in Land Records and issues faced by Entrepreneurs while purchasing and managing Land in Himachal Pradesh: A Comprehensive Legal and Economic Analysis - Jain, Lalit; Verma, Meenu (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper conducts a comprehensive legal and economic analysis of the complexities in Himachal Pradesh’s land records system and their adverse impact on entrepreneurial confidence in land acquisition under Section 118 of the Himachal Pradesh Tenancy and Land Reforms Act, 1972. The study identifies key procedural bottlenecks, ambiguous judicial interpretations, bureaucratic inefficiencies, and policy inconsistencies that deter industrial investment and economic development in the state. Through case studies, empirical data, and an examination of judicial precedents, the paper highlights how regulatory constraints—designed to protect agricultural land—often create unintended barriers for legitimate investors. The analysis also explores the socio-economic implications of these restrictions, including stalled projects, litigation risks, and reduced private sector participation in the state’s industrialization. The study concludes with policy recommendations to streamline land acquisition processes, enhance transparency in land records, and strike a balance between investment facilitation and agrarian protections. Proposed reforms include digital land record modernization, single-window clearances, and amendments to Section 118 to accommodate industrial growth while safeguarding local interests.